A Phytochemical Study of Andaliman (Zanthoxylum acanthopodium) for Contextual Chemotaxonomy Learning in Biology Education - Aswita Mardohar Hasibuan; Suyitno Aloysius; Paidi Paidi (Jurnal Penelitian Pendidikan IPA, 2026)
The andaliman (Zanthoxylum acanthopodium), also known locally as toba-toba, is a species endemic to North Sumatra, Indonesia, possessing a significant diversity of phytochemical compounds. This study aims to conduct a systematic review of the phytochemical content of andaliman and evaluate its potential for developing contextual biology education, specifically the topic of chemotaxonomy at the secondary education level. The research employed a systematic literature review protocol based on a search of national and international journals published between 2015 and early 2025. The results indicate significant phytochemical variation in andaliman (especially essential oils, alkaloids, flavonoids, saponins, and terpenoids) in highland populations, supporting the concept of chemotaxonomy. Although chemotaxonomy is globally established, its integration into science education in Indonesia, particularly in teaching plant classification using local phytochemical data, remains limited. This gap highlights the potential for developing biology teaching materials that integrate taxonomic concepts with local wisdom, which can substantially enhance scientific literacy and foster an appreciation for Indonesia's biodiversity.